The Role of Community in Increasing Public Awareness of Disaster Education: A Literature Review - Diansasnita, Aisha; Husna, Fahrun Nisa Sifaul Husna; Fitrah, Iftitah Hanim Tarisa Fitrah; Khoiroh, Mazroatul Khoiroh Ummah (Tarqabin Nusantara Group, 2024)
Indonesia has a high potential for disasters, both natural and non-natural, such as landslides, floods, earthquakes, tsunamis and erupting mountains. A major factor that causes disasters other than natural conditions is the lack of public knowledge about disasters. The role of communities and communities in disaster education is an essential aspect of shaping the socialization and skills needed in dealing with disaster threats. Community roles in disaster education include various aspects, such as community empowerment, skill and insight development, and development of a disaster risk-oriented curriculum design. Community Based Disaster Management (CBDM) is an effort that requires a series of efforts in interpreting their own disaster threats and risks, prioritizing disaster risk reduction, reducing, monitoring and evaluating their own performance in disaster reduction efforts. Community-based disaster helps communities organize themselves to be independent in facing disasters both pre-disaster, when a disaster occurs, and post-disaster. The community challenge in fostering community awareness of disaster education is to increase community awareness and ability to deal with disasters with the aim of minimizing or mitigating the risks or impacts caused by disasters. Some efforts that can be made to help communities become more prepared and alert in the face of disasters are as follows education and training, disaster mitigation, development of disaster response communities, disaster preparedness school education, disaster aware community, and disaster preparedness cadet program (Tagana).